Effectiveness of the Daniel Model in Enhancing Primary Students’ Learning of Cybersecurity Concepts - Ali A. Al-Barakat; Rommel M. AlAli; Omayya M. Al-Hassan; Eid M. Kanaan; Yusra Z. Aboud; Ali K. Abdullatif (Emerging Science Journal, 2025)
This study investigated the effectiveness of Daniel's Model in teaching cybersecurity concepts to ninth-grade students in Amman, Jordan. A quasi-experimental design with two groups was employed; the experimental group received instruction based on Daniel's model, while the control group followed traditional teaching methods. The sample consisted of 120 students, was selected from ten international schools via convenience sampling, and was randomly assigned to the groups. Data were collected using a 33-item knowledge test covering four key domains of cybersecurity. Analysis in SPSS included an independent samples t-test and a paired samples t-test; in addition, effect size (η²) was calculated to understand the magnitude of the model impact. A higher score of digital threat knowledge and skills in terms of prevention, ethical behaviors, and data protection related to the model taught was noticeable among the experimental group, since the effect size (η²) varied from large (0.34) to very large (0.62). Also, in the delayed test, the experimental group showed no decline in performance, demonstrating that the model was effective in teaching knowledge and digital practices. Considering the results, it is recommended that Daniel's Model, combined with interactive techniques and scenario building, be integrated in teaching digital ethics and use of technology, in addition to training teachers on systematic implementation of desired, sustained outcomes of the model.